2013
DOI: 10.1063/1.4801960
|View full text |Cite
|
Sign up to set email alerts
|

Electromechanical and magnetic properties of BiFeO3-LaFeO3-CaTiO3 ceramics near the rhombohedral-orthorhombic phase boundary

Abstract: BiFeO 3 -LaFeO 3 -CaTiO 3 ceramics have been studied by X-ray diffraction, magnetization measurements, and piezoresponse force microscopy (PFM). The compositional ranges of the polar, antipolar, and non-polar phases have been estimated. PFM measurements testify gradual decrease of piezoelectric response in Bi 0.85 x La 0.15 Ca x Fe 1 x Ti x O 3 system with Ca/Ti content increase, except a narrow concentration region near polar-antipolar phase boundary where piezoelectric signal shows maximum value. It is found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
9
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(12 citation statements)
references
References 39 publications
3
9
0
Order By: Relevance
“…The phase coexistence state is associated with increased mechanical compliance resulted in enhanced elastic and piezoelectric properties of the compounds as confirmed by the Piezoresponse Force Microscopy measurements in Bi 0.875 Pr 0.125 FeO 3 [14]. Enhanced electromechanical properties have also been detected in Bi 1-x RE x FeO 3 compounds series (RE = La, Nd, Sm) for the compositions near the morphotropic phase boundary [5,19] which verify the results of theoretical estimations [20,21].…”
Section: Three -Phase Coexistence Regionsupporting
confidence: 70%
“…The phase coexistence state is associated with increased mechanical compliance resulted in enhanced elastic and piezoelectric properties of the compounds as confirmed by the Piezoresponse Force Microscopy measurements in Bi 0.875 Pr 0.125 FeO 3 [14]. Enhanced electromechanical properties have also been detected in Bi 1-x RE x FeO 3 compounds series (RE = La, Nd, Sm) for the compositions near the morphotropic phase boundary [5,19] which verify the results of theoretical estimations [20,21].…”
Section: Three -Phase Coexistence Regionsupporting
confidence: 70%
“…The coexistence of structural phases is accompanied by a decrease in the elastic modulus and leads to an improvement of the piezoelectric properties, which is confirmed by scanning atomic force microscopy measurements in the piezoelectric response mode [16]. A significant improvement in the electromechanical properties was also revealed in solid solutions Bi 1 ⎯ x RE x FeO 3 (RE = La, Nd, Sm) with compositions near the morphotro pic phase boundary [9,21], which is consistent with the results of theoretical studies [22,23].…”
Section: Three Phase Structural Statesupporting
confidence: 53%
“…6,7 It has been recently demonstrated that a polar-to-non-polar phase transition with associated enhancements in the electromechanical response can be induced by the isovalent substitution of Bi 3þ with rare-earth elements, such as La 3þ and Sm 3þ . [8][9][10][11][12] The structure of BFO substituted with rare-earth compositions has been extensively studied by integral methods, such as Rietveld refinement of X-ray Diffraction (XRD) patterns, and additional methods [13][14][15] and only a few reports by local methods, such as transmission electron microscopy, have been published. [15][16][17][18] The phases that appear in the close proximity to the MPB are polar R3c, non-polar P nma , and antipolar P bam phases.…”
Section: Introductionmentioning
confidence: 99%